PENGARUH MEDIA PETA KONSEP DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR DAN DAYA INGAT SISWA PADA MATERI HIDROLISIS GARAM KELAS XI MIPA SMA NEGERI 7 PONTIANAK - Chairunisa Zakiyatun; Cawang Cawang; Rizmahardian Azhari Kurniawan (Universitas Muhammadiyah Pontianak, 2017)
ABSTRACTThe learning process centered on teachers thus leading students cannot think by themselves and build own knowledge so that students easily forget any lesson taught that resulted in poor study results. The learning process and environment which involves students participate actively is required. Therefore, this study examined the differences in the results of learning and memory of students taught with and without media concept maps in cooperative learning model NHT on the material salt hydrolysis. This study included a quasi-experimental design with Nonequivalent Control Group Design. The population in the study were all students of Mathematics XI consist of four classes with the number of students to 160 people. Samples were taken using purposive sampling with class XI MIPA1 as an experimental class and class XI MIPA2 as controls. Collecting data using measurement techniques, direct observation, and direct communication, while the data collection tool is a test description, the observation sheet and interview guidelines. Based on test data analysis using non-parametric Mann-Whitney U showed there were differences in the results of student learning and memory. Effect size obtained for the results of student learning and memory was 0.44 and 0.85 including in the criteria for medium and high, which affact to 17.00% towards learning outcomes of students and 30.23% of the students' memory.Keywords: memory, learning outcomes, salt hydrolysis, media concept maps, cooperative learning model NHT